Las primeras historias naturales de las Filipinas (1583-1604) - José Pardo-Tomás (Nuevo mundo - Mundos Nuevos, 2019)
The paper is based on the hypothesis that the Philippines was a territory colonized from New Spain and served as experience, accumulation, memory and practice for other spaces colonized from New Spain, mainly the North of Mexico and California. Although the Jesuits hegemonized the missionary-colonizing voice in those territories (the Philippines first, then the North), there were precedent ways of writing the natural history that the Jesuits knew, learned and, finally, appropriated and adapted. The paper presents one of the first attempts of writing the natural history of the Philippines, Antonio de Morga's Sucesos de las Islas Filipinas – published in Mexico, in 1609, but written between 1595 and 1603 – to compare it with the first natural history of the Philippines produced by a Jesuit, Pedro Chirino, published in Rome, in 1604.